Evolution of Phototrophy in the Chloroflexi Phylum Driven by Horizontal Gene Transfer - Ward, Lewis M.; Hemp, James; Shih, Patrick M.; McGlynn, Shawn E.; Fischer, Woodward W. (Frontiers in Microbiology, 2018)
The evolutionary mechanics behind the extant distribution of photosynthesis is a point of substantial contention, with hypotheses ranging from its presence in the last universal common ancestor and massive gene loss in most lineages, to a later origin followed by extensive horizontal gene transfer into the extant phototrophic clades, or intermediate scenarios that incorporate aspects of both end-members. Here, we report the discovery of ten new draft genome sequences of members of the Chloroflexi phylum from metagenomic sequencing of microbial mats in Japanese hot springs; these new taxa form a metabolically diverse, monophyletic clade sister to the Anaerolineae class that we term Candidatus Thermofonsia. Comparisons of organismal (based on conserved ribosomal) and phototrophy (reaction center and bacteriochlorophyll synthase) protein phylogenies throughout the Chloroflexi demonstrate that this new class includes two lineages that acquired phototrophy via horizontal gene transfer (HGT) independently from different ancestral donors within the classically phototrophic Chloroflexia class. These results illustrate a complex history of phototrophy within this group, with metabolic innovation tied to HGT. These observations do not support simple hypotheses for the evolution of photosynthesis that require massive character loss from many clades; rather, HGT appears to be the defining mechanic for the distribution of phototrophy in many of the extant clades in which it appears.